2006
DOI: 10.1021/jp057447k
|View full text |Cite
|
Sign up to set email alerts
|

Ridge-Bridge Adsorption of Molecular Oxygen on Pt{110}(1 × 2) from First Principles

Abstract: The chemisorption of molecular oxygen on the missing-row reconstructed Pt[110](1 x 2) surface has been investigated using ab initio calculations based on spin-density functional theory. The calculated energetic, structural, vibrational, and electronic properties of the chemisorbed O2 species are discussed in terms of the available experimental data. We find that adsorption in the ridge-bridge site is strongly preferred on energetic grounds, relative to adsorption on the [111] microfacets or in the valley sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…The predicted adsorption energy of O 2 (E ad (O 2 )) on graphdiyne is about À3.27 eV, which is much higher than that for the end-on configuration of CO adsorption (À1.43 eV). The value of E ad (O 2 ) for O 2 adsorption on graphdiyne is also significantly higher than those obtained for O 2 adsorption on Pt(111) (À0.58 to À0.72 eV), 47 Pt(001) (À1.30 eV), 48 Pt(110) (À1.48 eV), 49 Pt 2 (À1.42 eV), 50 Pt 3 (À1.08 eV), 51 Au 7 and Au 9 (about À0.5 eV), 52 and Au 4 cluster (À0.24 eV), 51 Fe-(À2.09 eV), 23 Au-(À1.34 eV), 52 and Cu-embedded graphene (À2.67 eV), 25 and Pd(111) (0 eV), 51 suggesting the high adsorption ability of O 2 on the graphdiyne sheet. This strong ability of graphdiyne for O 2 adsorption will greatly benefit its high electrocatalysis performance in fuel cells (such as toward ORRs) as well as its high resistance to CO poisoning because stable adsorption of O 2 is necessary for ORRs and for removal of CO via its oxidation reaction.…”
Section: Resultsmentioning
confidence: 55%
“…The predicted adsorption energy of O 2 (E ad (O 2 )) on graphdiyne is about À3.27 eV, which is much higher than that for the end-on configuration of CO adsorption (À1.43 eV). The value of E ad (O 2 ) for O 2 adsorption on graphdiyne is also significantly higher than those obtained for O 2 adsorption on Pt(111) (À0.58 to À0.72 eV), 47 Pt(001) (À1.30 eV), 48 Pt(110) (À1.48 eV), 49 Pt 2 (À1.42 eV), 50 Pt 3 (À1.08 eV), 51 Au 7 and Au 9 (about À0.5 eV), 52 and Au 4 cluster (À0.24 eV), 51 Fe-(À2.09 eV), 23 Au-(À1.34 eV), 52 and Cu-embedded graphene (À2.67 eV), 25 and Pd(111) (0 eV), 51 suggesting the high adsorption ability of O 2 on the graphdiyne sheet. This strong ability of graphdiyne for O 2 adsorption will greatly benefit its high electrocatalysis performance in fuel cells (such as toward ORRs) as well as its high resistance to CO poisoning because stable adsorption of O 2 is necessary for ORRs and for removal of CO via its oxidation reaction.…”
Section: Resultsmentioning
confidence: 55%
“…Using DFT calculations, we found that O 2 is strongly chemisorbed on the C 59 N (–0.32 ∼ −0.84 eV for CN site and −0.66 ∼ −0.99 eV for CC site depending on the various adsorption sites, see Figure S1 and Table S1 in Supporting Information). Compared to those on Pt(111) (–0.58 ∼ −0.72 eV), Pt(110) (–1.48 eV), Pt(001) (–1.30 eV), Pt clusters (–0.72 eV for Pt 2 and −1.08 eV for Pt 3 ), Au clusters (–0.24 eV for Au 4 , ∼ −0.50 eV for Au 7 and Au 9 , −0.60 eV for Au 29 , −0.99 eV for Au 38 ), Pt‐embedded graphene (–1.34 eV), Cu‐embedded graphene (–2.67 eV), Fe‐embedded graphene (–2.09 eV), Au‐embedded graphene (–1.34 eV), the strong ability of C 59 N fullerene for O 2 adsorption (–0.32 ∼ −0.99 eV) creates its possibility as a high active and metal‐free catalyst for ORR and CO oxidation. Two species of O 2 activation on the C 59 N fullerene can be examined: superoxide and peroxide.…”
Section: Resultsmentioning
confidence: 99%
“…The stepped Pd{211} surface is concluded to be more reactive towards oxygen dissociation than either of the two flat surfaces, Pd{100} and Pd{111}, where, in the latter case at least, molecular adsorption is weak and the dissociation itself is an activated process. 145 Earlier calculations by Junell et al, 146 reporting potential energy surfaces for the stepped Pd{110} surface, had revealed molecular chemisorption minima corresponding to several different adsorption geometries, the most favourable being a ridge bridge site similar to that found by Petersen et al 96 on Pt{110}-(1 Â 2); the smallest barrier to dissociation was found to be 0.17 eV relative to the gas-phase molecule, and occurs with the O-O bond lying along the trough. 146 Note that the clean Pd{110} surface is unreconstructed, in contradistinction to the missing-row reconstruction of the clean Pt{110} surface.…”
Section: Palladiummentioning
confidence: 70%
“…86 In agreement with the original background-dosing studies, intact molecular adsorption of ethane and propane was reported in supersonic beam experiments conducted at a surface temperature of 95 K. 84,87 During the present decade, a succession of detailed experiments on alkane dissociation and oxidation over Pt{110}-(1 Â 2) have emerged from the Cambridge group, again making use of the supersonic molecular beam technique to extract detailed information on the adsorption and reaction dynamics of methane [88][89][90][91][92] and ethane. 93,94 Throughout the same period, parallel theoretical efforts have addressed the adsorption and/or dissociation of methane, 25,26,36,91 ethane 34,35,95 and oxygen 96 on the same surface, by means of DFT calculations whose results we summarise below.…”
Section: Platinummentioning
confidence: 99%
See 1 more Smart Citation